Peningkatan Produksi Dan Efisiensi Teknis Usahatani Padi Sawah Pada Lahan Terbatas Di Daerah Istimewa Yogyakarta - Ismiasih Ismiasih; Jamhari Jamhari; Fakhrisha Nur Mahiswari (Politeknik Negeri Lampung., 2025)
Rice is an agricultural commodity that plays an important role in meeting the basic needs of people in Indonesia. Along with population growth, rice consumption in Indonesia continues to increase. However, the availability of agricultural land is not commensurate with the increase in population, on the contrary, its availability is decreasing. One way to increase rice productivity is land intensification through improvements in the management of production factors by using them efficiently. This research aims to determine: 1) the determining factors for rice farming production, 2) the determining factors for technical efficiency and technical inefficiency of rice farming in the Special Region of Yogyakarta (DIY). The data used is secondary data sourced from the results of the 2013 agricultural census with a sample of 3,751 farmers. Data analysis uses the multiple linear regression method estimated using Ordinary Least Square (OLS) to determine the determining factors of rice farming production. Technical efficiency is analyzed using a stochastic frontier model estimated with Maximum Likelihood Estimation (MLE). Based on the results of the analysis, it is known that rice farming production in DIY is influenced by harvest area, NPK fertilizer, organic fertilizer, pesticides, labor, irrigation systems, superior varieties, seasons and climate change. Factors that have a significant influence on the technical efficiency of rice farming are harvest area, NPK fertilizer, organic fertilizer, labor, irrigation systems, superior seeds and pesticides. The determining factors for technical inefficiency are age, education, government assistance, counseling, and field schools.